أثر بنک المعرفة المصرى على بناء وتنمية مقتنيات المکتبات الطبية الجامعية بجامعة المنوفية : دراسة مسحية مقارنة - سهير السيد بسيونى (المجلة الدولية لعلوم المكتبات والمعلومات)
The study deal with the impact of the Egyptian Knowledge Bank on theprocess of building and developing the holdings of university medical libraries atthe University of Menoufia. Medicine, National Liver Institute, College ofPharmacy, College of Health Medical Sciences Technology, College of Nursing,College of Veterinary Medicine, Technical Institute of Nursing), at MenoufiaUniversity, and also made a checklist, with description and analysis of those datain search of four main elements (development of holdings Libraries - EgyptianKnowledge Bank - Global Databases - University Medical Libraries), and afterresearch and data analysis, the most important results of the study were that thetotal number of books in the libraries of the medical sector faculties at MenoufiaUniversity reached the scope of the study, which were acquired in the time period2015-2020 (917). A book, and that the number of what was found of them in theKnowledge Bank is (87) books, and on the other hand, in the databases of theEgyptian Knowledge Bank there are many sources that are not found in medicallibraries, and that no There is a systematic plan for medical libraries, the scope ofthe study, to benefit from the Egyptian Knowledge Bank in the process of buildingand developing their holdings. Medical Center at Menoufia University byappointing a work team from within the library and assigning it to daily searchthrough the databases of the Egyptian Knowledge Bank to identify everything thatis new, and to make decisions either to upload it and add it to the general indexor to determine direct availability through the Knowledge Bank.